Analysis of the Transcriptome of the Infective Stage of the Beet Cyst Nematode, H. schachtii. - John Fosu-Nyarko; Paul Nicol; Fareeha Naz; Reetinder Gill; Michael G K Jones (PLoS ONE, 2016)
The beet cyst nematode, Heterodera schachtii, is a major root pest that significantly impacts the yield of sugar beet, brassicas and related species. There has been limited molecular characterisation of this important plant pathogen: to identify target genes for its control the transcriptome of the pre-parasitic J2 stage of H. schachtii was sequenced using Roche GS FLX. Ninety seven percent of reads (i.e., 387,668) with an average PHRED score > 22 were assembled with CAP3 and CLC Genomics Workbench into 37,345 and 47,263 contigs, respectively. The transcripts were annotated by comparing with gene and genomic sequences of other nematodes and annotated proteins on public databases. The annotated transcripts were much more similar to sequences of Heterodera glycines than to those of Globodera pallida and root knot nematodes (Meloidogyne spp.). Analysis of these transcripts showed that a subset of 2,918 transcripts was common to free-living and plant parasitic nematodes suggesting that this subset is involved in general nematode metabolism and development. A set of 148 contigs and 183 singletons encoding putative homologues of effectors previously characterised for plant parasitic nematodes were also identified: these are known to be important for parasitism of host plants during migration through tissues or feeding from cells or are thought to be involved in evasion or modulation of host defences. In addition, the presence of sequences from a nematode virus is suggested. The sequencing and annotation of this transcriptome significantly adds to the genetic data available for H. schachtii, and identifies genes primed to undertake required roles in the critical pre-parasitic and early post-parasitic J2 stages. These data provide new information for identifying potential gene targets for future protection of susceptible crops against H. schachtii.